REKONTEKSTUALISASI SEMIOTIKA FERDINAND DE SASSURE DALAM MEMAKNAI KONSEP CAHAYA SEBAGAI HIDAYAH: ANALISISQ.S AN-NUR: 35 - Djamali Mokoginta (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
This article examines the recontextualization of Ferdinand de Saussure's semiotics in understanding the concept of light as guidance, focusing on the analysis of QS. An-Nur: 35. The symbol of "light" in this verse is understood as a complex metaphor symbolizing divine guidance (hidayah), spiritual presence, and inner enlightenment. This study employs Saussure's concept of signs, with the signifier as the physical representation and the signified as the spiritual meaning. In the religious context, the symbol of light represents the relationship between Allah and humanity through moral guidance, purification of the soul, and the dissemination of faith. The research also explores how the symbol of light is recontextualized in Islamic culture through traditions, art, and education, as well as its relevance in contemporary life, such as Islamic psychology and intercultural dialogue. This article offers a profound new perspective on understanding the physical and spiritual dimensions of light as a sign of divine wisdom.